2018
DOI: 10.1136/bmj.k1959
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of text message based, diabetes self management support programme (SMS4BG): two arm, parallel randomised controlled trial

Abstract: ObjectiveTo determine the effectiveness of a theoretically based and individually tailored, text message based, diabetes self management support intervention (SMS4BG) in adults with poorly controlled diabetes.DesignNine month, two arm, parallel randomised controlled trial.SettingPrimary and secondary healthcare services in New Zealand.Participants366 participants aged 16 years and over with poorly controlled type 1 or type 2 diabetes (HbA1c ≥65 mmol/mol or 8%) randomised between June 2015 and November 2016 (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
135
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 40 publications
10
135
0
7
Order By: Relevance
“…Extensive end‐user engagement and formative work was undertaken to inform the development of the programme, which has been previously described . SMS4BG was found to be acceptable and perceived to be useful in a small pilot study , and a pragmatic randomized controlled trial (RCT) found it to result in modest but significant improvements in glycaemic control at 9 months' follow‐up .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive end‐user engagement and formative work was undertaken to inform the development of the programme, which has been previously described . SMS4BG was found to be acceptable and perceived to be useful in a small pilot study , and a pragmatic randomized controlled trial (RCT) found it to result in modest but significant improvements in glycaemic control at 9 months' follow‐up .…”
Section: Introductionmentioning
confidence: 99%
“…1 Of 21 secondary outcomes assessed, there were statistically significant improvements in four: foot care behaviour, perceived support for diabetes management, health status and how much patients experienced diabetes-related symptoms.…”
mentioning
confidence: 98%
“…1 In this trial, the authors accepted that the reductions in HbA 1c were not considered to be clinically important, with an average reduction of 4.2mmol/mol (0.4%). However, they report that the programme showed a high level of acceptability, with most participants finding the intervention useful and willing to recommend it to others.…”
mentioning
confidence: 99%
See 2 more Smart Citations